Thinking with Trees: Researching Religion in the Anthropocene - Wiesgickl, Simon (Worldviews, 2025)
This article presents anthropological concepts, ideas and discussions that deal with the relationship between humans and the more-than-human world. The focus is on the relationship between trees and human people in the Anthropocene. Trees have been a classical topic for religious studies and anthropology and environmental humanities have embraced plant studies and multispecies research in the last decades. It is argued that those newer perspectives are relevant to religious studies and can inspire a renewed reflection on concepts such as ‘animism’, ‘agency’ and ‘person’. On the other hand, critical discussion within the field of religious studies might help to sharpen some reflection and avoid the pitfalls of a colonial history of terms like "animism". It is precisely the changing interplay and the multitude of relationship concepts between trees and humans that lends itself not only to a comprehensive review of the material, but also to tough theoretical and methodological discussions. The author’s field of research in Northeast India and its intertwined history of trees and human persons is showcased and ways of critical research tested. Finally, the argument is developed, that trees are good to think with and open promising intersections of religion and ecology.